Acinetobacter baumannii Response to Host-Mediated Zinc Limitation Requires the Transcriptional Regulator Zur - Mortensen, Brittany L. (American Society for Microbiology, 2014)
Acinetobacter baumannii is a leading cause of ventilator-associated pneumonia in intensive care units, and the increasing rates of antibiotic resistance make treating these infections challenging. Consequently, there is an urgent need to develop new antimicrobials to treat A. baumannii infections. One potential therapeutic option is to target bacterial systems involved in maintaining appropriate metal homeostasis, processes that are critical for the growth of pathogens within the host. The A. baumannii inner membrane zinc transporter ZnuABC is required for growth under low-zinc conditions and for A. baumannii pathogenesis. The expression of znuABC is regulated by the transcriptional repressor Zur. To investigate the role of Zur during the A. baumannii response to zinc limitation, a zur deletion mutant was generated, and transcriptional changes were analyzed using RNA sequencing. A number of Zur-regulated genes were identified that exhibit increased expression both when zur is absent and under low-zinc conditions, and Zur binds to predicted Zur box sequences of several genes affected by zinc levels or the zur mutation. Furthermore, the zur mutant is impaired for growth in the presence of both high and low zinc levels compared to wild-type A. baumannii. Finally, the zur mutant exhibits a defect in dissemination in a mouse model of A. baumannii pneumonia, establishing zinc sensing as a critical process during A. baumannii infection. These results define Zur-regulated genes within A. baumannii and demonstrate a requirement for Zur in the A. baumannii response to the various zinc levels experienced within the vertebrate host.